Pharmacovigilance : Critique and Ways Forward - Edwards, I. Ralph; Lindquist, Marie (Springer International Publishing : Imprint: Adis, 2017)
Written by experienced authors, this book offers expert personal views on what the current problems in pharmacovigilance are and how they should be solved. This book stems from thoughts and ideas discussed in a series of meetings of the International Society of Pharmacovigilance (ISoP), where concerns were raised that the current pharmacovigilance system is not delivering optimally to improve therapeutics in clinical practice. Pharmacovigilance of the future must be an active and integral part of health care delivery, and focus more on science and practices that support health professionals and patients in day-to-day care situations. To achieve this, a dynamic and sustainable development of vigilance must take precedence over the current excessive preoccupations with data processing and regulations; all aspects of medicines use and their effects need to be considered; and all stakeholders must be involved and engaged in an open and constructive debate. The work is essential reading for anyone who has an interest in safer use of medicines. It is intended to be equally challenging and rewarding, and sets out to stimulate a continuous debate on how pharmacovigilance can better meet the needs of health professionals and patients to achieve the aim of wise therapeutic decision making.
Keywords: Medicine.; Pharmacy.; elektronické knihy; electronic books